Pendidikan Islam dan Tantangan Globalisasi - Nasucha, Juli Amaliya (Program Studi Doktor Pendidikan Agama Islam dan Program Magister Pendidikan Agama Islam, Pascasarjana Universitas Islam Negeri Sunan Ampel, 2016)
Globalization is a historical phase that wants to eliminate the limits of space and time in human life, covering the aspects of economy, communication, politics, and social. Globalization has positive and negative effects. The positive impacts among other things are opening up a wide range of convenience and comfort both in the economic environment, information, technology, social, and psychology; while the negative impactsarethe occurrence of dislocation, dehumanization, secularization, and so forth. Therefore, we should be able to optimize the positive impacts and minimize the negative impacts on the life. The right attitude in facing globalization is the proportional attitude, that isneither reject absolutely nor accept absolutely; taking the good one and developing it, while those which are not good are rejected and removed. Whereas for Islamic educational institutions, there is a strategic role in facing the challenges of globalization. Islamic educational institutions play a role as the heir to the culture through the education of valuessystem, beliefs, knowledge, norms, customs, and behaviors that have been entrenched and passed on one generation to the next.